Stretching the golden thread: the impact of Brexit on the presumption of innocence - Michelle Coleman (Contemporary Challenges to Human Rights Law, 2020)
For the past several years, the United Kingdom has been consumed by the Brexit debate. While the popular and political debate has been far ranging, one thing that seems to have been overlooked is the United Kingdom’s responsibility to follow European Union Directives and what effect no longer following the directives will have on the country. Directives provide minimum standards for European Union member states to follow, which enhances freedom of movement and goods throughout the Union and allows for consistent application of human rights between the various countries. While it seems obvious that the United Kingdom will no longer follow European Directives once Brexit occurs, what is not obvious is the effect that will have on the people. This is particularly important since directives commonly deal with issues of human rights.In 2016, European Directive 2016/343 came into force, which provides cutting-edge rules on what the human right to the presumption of innocence entails and when it should apply. While the United Kingdom does follow the presumption of innocence in criminal trials there are some areas that should be strengthened in order to comply with the European Directive and to provide adequate protections for those accused of crimes. With Brexit looming, however, it appears that the United Kingdom will not be taking steps to comply with the Directive, and that the presumption of innocence measures within England will remain as they currently are. This chapter examines how failing to conform with this Directive will affect the United Kingdom. First, it describes and discusses the presumption of innocence as it currently stands in England and Wales. The chapter then examines the 2016 Directive with regard to its requirements for the presumption of innocence and in what ways it provides a cutting edge understanding of this right. The next part of the chapter will highlight and comment on areas of the law in England and Wales where the Directive could help strengthen the presumption of innocence. Specifically there will be discussion about the use of adverse inferences in exercising the right to silence, the use of the dock in the courtroom, and the allowance of Terrorist Prevention and Investigation Measures (TPIMs) against suspects. Finally the chapter concludes that leaving the European Union will mean that the United Kingdom is missing an opportunity to become a world leader with regard to the right to the presumption of innocence.